The multidisciplinary process leading to return from underperformance and sustainable success in the world`s best cross-country skier - Strøm Solli, G.; Tonnessen, E.; Sandbakk, Ø. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To investigate the factors associated with underperformance and the subsequent changes in training characteristics and supportive actions when returning to the world`s best cross-country skier. Methods: The participant is the most decorated winter Olympian, with 8 Olympic gold medals, 18 World Championship titles, and 114 World Cup victories. Training data were categorized by training form (endurance, strength, and speed); intensity (low, moderate, and high); and mode (running, cycling, and skiing/roller skiing). In addition, test data were retrospectively analyzed, and interviews were performed with the participant and her support team. Results: After the competitive season, the participant had 8 weeks without systematic training and an evaluation process aiming to detect the factors contributing to underperformance. Here physiological, technical, and psychological challenges were detected. As a consequence, the participant included less high-intensity training (1.2 vs 2.1 sessions/wk, P=.011); more moderate-intensity training (0.9 vs 0.4 sessions/wk, P=.016); and more low-intensity training (6.9 vs 5.9 sessions/wk, P=.036) during the general preparation phase but with similar total endurance training load as previous season. In addition, more strength training (1.6 vs 1.1 h/wk, P=.036) and new ski-specific strength exercises were included. Finally, the athlete`s autonomy when planning and adjusting training was increased, nontraining stressors were reduced, more frequent testing was included, systematic mental training was initiated, her nutritional strategy was adjusted, and her asthma treatment was optimized. Conclusions: Overall, the current case study could be used as a framework for the holistic approach to treating an overtraining condition and for generation of new hypothesis in this exiting area.